Adaptasi Perkawinan Lintas Agama - Syam, Nia Kurniati; Mulyana, Deddy; Rachmiatie, Atie; Yusuf, Pawit M. (STAI Miftahul Ula Nganjuk, 2017)
Abstract: This research is a field study on the phenomenon of interfaith marriage, using subjective paradigm-Phenomenology interpretive method and theory of symbolic interaction to identify the types of motifs, adaptation and religious symbols in interfaith marriage. Data collection techniques natural setting, observation, interviews and documentation. The research objective is to explore apamotif interfaith marriage, how adaptations in marriage and religious symbols on families of different religions. The results showed that the pair families of different religions have a motive of love, appearance, comfort, education and the economy, in the adaptation of the marital interfaith marriage portion has a communication climate of consensus, where children married couples of different religions to adapt among married couples that have implications the decision to follow the religion of one parent and or choice in child later handed over to an adult. The authority of the couple in the election decision religion children found their own authority as a husband and wife having legitimacy, had a religious reference. In connection with religious symbols for families of different religions is not a sacred thing. Interfaith families have a high tolerance. Knowledge and strengthening the values ââof their respective religions encourage the growth of tolerance and high empathy.